Migration from Turkey and the uncertainty of the accession of Turkey to the EU - Demet Beton; Glenn Jenkins (Queen's University, Department of Economics, 2008)
There is a fear that if Turkey were given admission to the EU massive migration to the other member countries of the EU would result. This paper develops a theoretical framework for the migration decision that takes into consideration the impact on uncertainty of some of the important economic and social variables that are addressed by the EU membership and institutions. It emphasizes future expectations of living conditions and the level of uncertainty associated with them as a key variable in making migration decisions. It suggests that the more prosperous and stable Turkey is expected to be in the future the less likely a person will now want to migrate. Hence, the greater certainty now that Turkey will gain admission in to EU, the more attractive is it for potential migrants to remain in Turkey. This framework suggests that measures to hinder Turkey's entry into the EU by having national referendums to approve its entry will increase the uncertainty of the future economic and social prospects in Turkey and will encourage migrants to migrate now to the member countries of the EU.
Keywords: F22; J61; 330; Turkey; Migration; Uncertainty; Accession; European Union; Internationale Wanderung; Internationale Arbeitsmobilität; Einwanderungsrecht; EU-Erweiterung; Türkei; EU-Staaten